Površinska obdelava materiala - obstreljevanje s kroglicami - Zupanc, Uroš (Vakuumist, 2008)
Shot peening has been an important and well-known surface cold-hardening process applicable to various machine parts and tool surfaces for quite a long time since it improves fatigue strength and corrosion resistance of the stressed surface. Because of plastic deformation, hardening by shot peening provides an increase in hardness and induces compressive residual stresses in the thin surface layer, which reduces material fatigue and prevents the generation and propagation of cracks.
Keywords: dinamična trdnost; korozijska odpornost; peskanje; površinska obdelava; utrjevanje